Evaluation of rhizosphere bacterial community of pineapple from different varieties and their potential as biocontrol agents for controlling bacterial heart rot disease / Muhammad Ikhwan Tajudin - Tajudin, Muhammad Ikhwan (Faculty of Plantation and Agrotechnology, 2018)
Pineapple (Ananas comosus) has play important roles as industrial crop after a recent years. Malaysia has various types of hybrid varieties including N36, Josapine and MD2 that had been classified as luxury fruit. The dependency of chemical application in controlling pest and disease have been rechecked to reduce cost and to provide sustainability to pineapple industry as well to increase quality and firmness of pineapple cultivar. Meanwhile, bacterial heart rot disease is an important as devastating bacterial disease of pineapple. Chemical control of the disease would be difficult, or it could lead to resistant of the pathogen as give negative effect to the environment. Hence, alternative way of using chemical is biological control agent. The bacteria were isolated from roots of healthy pineapple, characterized by macroscopic and microscopic observations which shown four different species. The collected data were analysed by using one way ANOVA for population mean. All bacterial isolates were tested for their potential as biological agent for inhibiting the growth of pathogen via diffusion well method. The result showed that bacterial isolates named as B1 had the highest mean of inhibition zone (29%) against the pathogen followed by B2 isolates. This finding suggested that rhizosphere bacteria have potential to be used and explored as biological control agent for controlling bacterial heart rot disease on pineapple.